(untitled) (International Journal of Contemporary Security Studies, 2023)
This paper presents briefly a holistic approach to reducing flood risks using the nature-based solutions. This approach takes into account not only the reduced risk as the primary goal of flood mitigation, but also involves other goals such as the protection of the environment, human well-being, socio-economic goals etc. The Tamnava River basin is used as a pilot case to demonstrate the methodology of such an approach, resulting from the work within the RECONECT project from the EU Horizon 2020 programme. The paper presents preliminary results for the Tamnava River basin by considering several scenarios for flood mitigation measures and potential benefits from these measures in flood risk reduction and in improved ecosystem services in the basin. The methodology includes monetary valuation of the effects of the proposed flood mitigation measures in terms of the avoided damages, as well as of the secondary benefits from the erosion control by additional afforestation. The latter also provides basis for preliminary valuation of all relevant ecosystem services in the basin, thus indicating the value of the basin’s natural capital. Such an evaluation is important for the decision-making process on possible flood mitigation strategies.